Sort by

- Relevance
- |Time

...and h. You can see the latter as follows: f(x) = c . a^(d(x-h)) +

**k**=**c**. a^(dx) . a^(-dh) +**k**=**c**' . a^(dx) + k, where c' = c . a^(-dh) So we...2 Answers · Science & Mathematics · 06/04/2016

...prime, we may conclude that p|m. Writing m = cp for some integer c, we get (cp)^

**k**=**c**^k * p^k = p * n^k ==> n^**k**=**c**^k * p^(k-1). Since k > 1, we have...1 Answers · Science & Mathematics · 14/10/2009

...the constant. We know that initially, v(0) = 0, so: 0 = C - g*M/

**k****C**= g*M/k v(t) = (g*M/k)*(exp(-k*t/M) - 1) Now, v...1 Answers · Science & Mathematics · 28/03/2010

...the constant. We know that initially, v(0) = 0, so: 0 = C - g*M/

**k****C**= g*M/k v(t) = (g*M/k)*(exp(-k*t/M) - 1) Now, v...1 Answers · Science & Mathematics · 28/03/2010

...the constant. We know that initially, v(0) = 0, so: 0 = C - g*M/

**k****C**= g*M/k v(t) = (g*M/k)*(exp(-k*t/M) - 1) Now, v...1 Answers · Science & Mathematics · 28/03/2010

**k****C**= g*M/k v(t) = (g*M/k)*(exp(-k*t/M) - 1) Now, v...2 Answers · Science & Mathematics · 29/03/2010

**k****C**= g*M/k v(t) = (g*M/k)*(exp(-k*t/M) - 1) Now, v...2 Answers · Science & Mathematics · 29/03/2010

...of the result ln (T - 21) = kt + C ..........................(1) ln (26 - 21) = 5*

**k**+**C**= ln(5) ln (41 - 21) = 0***k**+**C**= ln 20 ...........(2) 5k = ln(5) - ln(20) = ln(1...3 Answers · Science & Mathematics · 30/03/2013

...) = C/A*k/A - C/B*k/B = C*

**k**-**C***k = 0 So now we only have to show that if we start at point (x1,y1) and then...1 Answers · Science & Mathematics · 19/09/2009

hypergeometric distribution. use combinations sum C(12,

**k**)***C**(88,25-**k**)/**C**(100,25), k = 3 to 5 = .5786 <-----2 Answers · Science & Mathematics · 08/03/2014

##### Ad

related to**K.C**